Selecting Business Intelligence Solutions using Requirements Engineering - Carbell, Anna; Mann, Andreas (My University, 2019)
Business Intelligence (BI) is a collection of processes, technologies, and tools that aims to provide organizational value by triggering actions and decisions through well-presented information extracted from company data. Existing BI solutions on the market can be used to present the information. There is, however, no guidance in how to select an existing BI solution but there are many approaches to requirements engineering (RE) in BI which aim to build a BI solution from scratch. Therefore, this research investigated if existing methods for RE in BI also could be useful for selecting an existing BI solution based on the requirements the methods produced. The experience from doing so was used to understand what an appropriate method to select a BI solution could be. The results showed that the existing methods for RE in BI could be used but that they gave weak support in selecting an existing BI solution. Hence, there were more appropriate ways to select BI solutions that were recommended instead of the existing methods. Based on the lessons learned from applying existing methods in parallel and from studying BI solutions, a new method was designed with the purpose of selecting an existing BI solution. The new method consisted of five phases; a prestudy, feasibility study, market analysis, requirements elicitation, and BI solution selection (see Section 5.5). The new method was deemed to be a more appropriate way to select a BI solution than existing methods since it produced requirements and criteria in a hybrid approach that could be used to distinguish between BI solutions. The research was carried out on a real case at a global manufacturing company with headquarters in Stockholm, Sweden during Spring 2019.
Keywords: requirements engineering; business intelligence; requirements elicitation; KPI; BI solution